Human Cytomegalovirus Latency and Reactivation in Allogeneic Hematopoietic Stem Cell Transplant Recipients - Stern, Lauren; Withers, Barbara; Avdic, Selmir; Gottlieb, David; Abendroth, Allison; Blyth, Emily; Slobedman, Barry (Frontiers in Microbiology, 2019)
Human cytomegalovirus (HCMV) reactivation is a major infectious cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). HCMV is a ubiquitous beta-herpesvirus which asymptomatically infects immunocompetent individuals but establishes lifelong latency, with the potential to reactivate to a life-threatening productive infection when the host immune system is suppressed or compromised. Opportunistic HCMV reactivation is the most common viral complication following engraftment after HSCT and is associated with a marked increase in non-relapse mortality, which appears to be linked to complex effects on post-transplant immune recovery. This minireview explores the cellular sites of HCMV latency and reactivation in HSCT recipients and provides an overview of the risk factors for HCMV reactivation post-HSCT. The impact of HCMV in shaping post-transplant immune reconstitution and its relationship with patient outcomes such as relapse and graft-versus-host disease will be discussed. Finally, we survey current and emerging strategies to prevent and control HCMV reactivation in HSCT recipients, with recent developments including adoptive T cell therapies to accelerate HCMV-specific T cell reconstitution and new anti-HCMV drug therapy for HCMV reactivation after HSCT.